IMPLEMENTASI KEBIJAKAN TERHADAP PENANGANAN SAMPAH KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Amir, Ayu Lestari; Sapri, Sapri; Hardianti, Hardianti (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to determine the effect of Policy Implementation and to find out the supporting factors and inhibiting factor that affect the Implementation of Waste Handling Policies in Panca Rijang District, Sidenreng Rappang Regency. The population in this study was the total population in Panca Rijang District which amounted to 34.433 residents and the sample in this study was 100 respondents determined by using the Slovin formula and purposive sampling technique. The type of research used is quantitative research. Data collection techniques were carried out through observation, questionnaires, and literature studies. The data analysis technique is with the help of the IBM SPSS statistics 25 application. The results of this study indicate the results of the recapitulation of the policy implementation variables with a percentage of 75% in the good category and recapitulation of the waste handling variables with a percentage of 70,64% in the good category. Supporting factors and inhibiting factors for policy implementation on waste handling with a percentage of 72.7% are in the good category. Policy implementation affects waste handling, because the sifnificant value of 0.000 < 0,05, the Ho is rejected, so Ha is accepted. Supporting factors and inhibiting factors affect the implementation of waste handling policies, because the significant value of 0.000 < 0,05, then Ho is rejected and Ha is accepted.